2010
DOI: 10.1093/hmg/ddq025
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics, bioinformatics and targeted gene expression analysis reveals up-regulation of cochlin and identifies other potential biomarkers in the mouse model for deafness in usher syndrome type 1F

Abstract: Proteins and protein networks associated with cochlear pathogenesis in the Ames waltzer (av) mouse, a model for deafness in Usher syndrome 1F (USH1F), were identified. Cochlear protein from wild-type and av mice at postnatal day 30, a time point in which cochlear pathology is well established, was analyzed by quantitative 2D gel electrophoresis followed by mass spectrometry (MS). The analytic gel resolved 2270 spots; 69 spots showed significant changes in intensity in the av cochlea compared with the control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Previous 2D gel investigation identified a full-length isoform, as well as smaller isoforms with truncations of the N terminus. The molecular weight values of the predominant isoforms were 44 and 40 kDa [10,12]. Isoform-specific antibodies further identified the short truncated isoform CTP in the perilymph [10], and this isoform contains the N-terminal LCCL domain devoid of the C-terminal vWFA domain.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous 2D gel investigation identified a full-length isoform, as well as smaller isoforms with truncations of the N terminus. The molecular weight values of the predominant isoforms were 44 and 40 kDa [10,12]. Isoform-specific antibodies further identified the short truncated isoform CTP in the perilymph [10], and this isoform contains the N-terminal LCCL domain devoid of the C-terminal vWFA domain.…”
Section: Discussionmentioning
confidence: 95%
“…The potential effects that are conveyed by this molecular phenotype are currently unknown, but the observed change is counter to what has been reported in normal development. Our previous data indicated that the abundance of the full-length isoform p63s decreases relative to the abundance of the N-terminally truncated form p44s and p40s as a function of age in the rat, with the fulllength isoform predominant on DAB24 but decreased relative to the truncated form on DAB70 [11,12].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations